Concentration of apple juice using CO(2 )gas hydrate technology to higher sugar contents - Claßen, Timo; Jäger, Michael; Loekman, Soebiakto; Gatternig, Bernhard; Rauh, Cornelia; Delgado, Antonio (Innovative Food Science & Emerging Technologies, 2020)
This paper describes the application of CO2-hydrate technology for the concentration of apple juice towards industrially relevant levels. Assays were carried out in a stirred autoclave at 1-2 degrees C and 35 bars with rediluted apple concentrate in the range of 11 degrees Bx to 40 degrees Bx. A hydraulic pellet press was used to separate the hydrate from the concentrate, resulting in an almost complete sugar recovery. It was found that apple juice can be concentrated to 45 degrees Bx and beyond using this technique. Maximum hydrate conversion of up to 30% was achieved at an average concentration rate of 2.5-3 degrees Bx/h. Furthermore, an optimal juice to crystallizer volume ratio of 35% was found. The investigations also revealed the juice composition to interfere with the hydrate formation process to some extend. In the assays with constant water content, no decrease in the hydrate formation rate was observed until 30 degrees Bx. From this concentration onwards, however, the hydrate yield decreased steadily and amounted to only 15% M 40 degrees Bx.
CRIS-Team WoS Importer:2020-09-25

Ethene-induced temporary inhibition of grubbs metathesis catalysts - Scholz, Judith; Loekman, Soebiakto; Szesni, Normen; Hieringer, Wolfgang; Görling, Andreas; Haumann, Marco; Wasserscheid, Peter (dvanced Synthesis & Catalysis, 2011)
Grubbs-type catalysts were immobilized in form of supported ionic liquid phase (SILP) materials and applied in the gas-phase cross-metathesis of various substrates in order to study the effect of ethene on catalyst activity and stability in detail. From our theoretical and experimental findings we suggest that ethene causes temporary inhibition effects due to a reversible shift of ruthenium complexes from the productive catalytic cycle towards unproductive, dormant ruthenium species. By avoiding the presence of ethene, constant catalytic activity and selectivity for more than 20 days of continuous operation could be realized. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Flows due to pressure induced dissociation-formation of gas hydrates - Rodríguez Agudo, José; Kwon, Sinyoung; Saur, Roland; Loekman, Soebiakto; Luzi, Giovanni; Rauh, Cornelia; Wierschem, Andreas; Delgado, Antonio (IOP Conference Series: Materials Science and Engineering, 2017)
During the last decade, Gas Hydrates (GH) have attracted the interest of the scientific community for engineering applications. Carbon dioxide hydrate (CO2H), for instance, may play an important role for capture and sequestration methods in order to reduce global climate change. Despite the extensive literature, the transport phenomena involved during CO2H formation are not yet fully understood. CO2 transfer from gas or liquid phase to the bulk of water is expected to happen not only by molecular diffusion but also driven by natural convective currents induced by CO2 dissolution in water. Using particle tracer methods, we experimentally characterize the flow velocity of the bulk of water during CO2H formation. For that purpose, CO2H is grown inside an optical cell with a volume of 12 mL at various pressures and temperatures. Due to CO2 dissolution, convection currents are noticed prior to hydrate formation. Our experimental results point to a significant correlation between this process and the subsequent hydrate formation. Two well-differentiated hydrate growth patterns were observed depending on the hydrate induction time and the corresponding CO2 concentration distribution inside water. For long induction times, CO2 can be provided from the water phase resulting in rapid growth. Short induction times resulted in slow growth at the interface creating a solid barrier accompanied by a significant drop in the flow velocity. In some cases, the hydrate layer appeared to be unstable and convection could restar

Food technological potentials of CO2 gas hydrate technology for the concentration of selected juices - Seidl, Pia; Loekman, Soebiakto; Sardogan, Miray; Voigt, Erik; Claßen, Timo; Ha, Jawon; Luzi, Giovanni; Sevenich, Robert; Rodríguez Agudo, José; Rauh, Cornelia; Delgado, Antonio (High Pressure Research, 2019)
CO2 gas hydrate technology seems to be a gentle way to concentrate juices, especially comparing to evaporation processes which achieve high levels of concentration and is furthermore energetically favorable in contrast to freeze concentration processes. CO2 can form gas hydrates at around 30–80 bar and 274–283 K. For evaluating this new technology, it is not only important to know the phase equilibrium lines of commercial juices like apple and orange juices but also how the application of e.g. a bubble column affects the gas hydrate formation and separation from the concentrated product. In order to support the experimental outcome, numerical modeling seems suitable to understand the physical background of this novel concentration technology. This includes the simulation of temperature, velocity, pressure and concentration fields using finite volume technique. All three work packages combined will lead to a better understanding of the behavior of gas hydrate technology used to concentrate liquid foo
Keywords: Fruit juice; hydrate technology; food technology; gas hydrate; carbon dioxide/CO2 clathrate; CO2 hydrate

Potential Application of Innovative Gas Hydrate Technology in Fruit Juices Concentration Process - Loekman, Soebiakto; Claßen, Timo; Seidl, Pia; Luzi, Giovanni; Gatternig, Bernhard; Rauh, Cornelia; Delgado, Antonio (Proceedings of 2019 World Congress on Advances in Nano, Bio, Robotics, and Energy, 2019)

Review on the food technological potentials of gas hydrate technology - Claßen, Timo; Seidl, Pia; Loekman, Soebiakto; Rauh, Cornelia; Delgado, Antonio; Gatternig, Bernhard (Current Opinion in Food Science, 2019)
Gas hydrate technology has been known for a long time, but has only recently gained interest in food technology field. A major advantage for food technology applications are the gentle conditions under which products can be refined using gas hydrates, therefor not altering or damaging valuable product contents. This review discusses recent developments of hydrate applications for different areas of food technology for example concentration and purification processes, the preservation of foodstuff as well as novel product designs.
CRIS-Team Scopus Importer:2019-09-17
Keywords: Gashydrate; Lebensmitteltechnologie; Fruchsaftkonzentration

Use of a catalyst composition for olefin metathesis in the gas phase and procedure for the olefin metathesis in the gas phase. - Szesni, Normen; Müller, Stephan; Fischer, Richard; Wasserscheid, Peter; Haumann, Marco; Öchsner, Eva; Loekman, Soebiakto; Demin, Arthur (2010)
Highly efficient catalyst compns. for olefin metathesis such as manuf. of ethylene and 1-butene from propylene in the gas phase consist of ionic liqs. contg. dissolved catalysts and supported on inorg. compds. [on SciFinder(R)]
Keywords: inorg compd supported ionic liq catalyst soln olefin metathesis; ethylene butene manuf propylene metathesis reaction catalyst

Visually Based Characterization of the Incipient Particle Motion in Regular Substrates: From Laminar to Turbulent Conditions - Rodríguez Agudo, José; Han, Jiwon; Park, Jinyoung; Kwon, Sinyoung; Loekman, Soebiakto; Luzi, Giovanni; Lindenberger, Christoph; Delgado, Antonio; Wierschem, Andreas (Journal of Visualized Experiments, 2018)
Two different experimental methods for determining the threshold of particle motion as a function of geometrical properties of the bed from laminar to turbulent flow conditions are presented. For that purpose, the incipient motion of a single bead is studied on regular substrates that consist of a monolayer of fixed spheres of uniform size that are regularly arranged in triangular and quadratic symmetries. The threshold is characterized by the critical Shields number. The criterion for the onset of motion is defined as the displacement from the original equilibrium position to the neighboring one. The displacement and the mode of motion are identified with an imaging system. The laminar flow is induced using a rotational rheometer with a parallel disk configuration. The shear Reynolds number remains below 1. The turbulent flow is induced in a low-speed wind tunnel with open jet test section. The air velocity is regulated with a frequency converter on the blower fan. The velocity profile is measured with a hot wire probe connected to a hot film anemometer. The shear Reynolds number ranges between 40 and 150. The logarithmic velocity law and the modified wall law presented by Rotta are used to infer the shear velocity from the experimental data. The latter is of special interest when the mobile bead is partially exposed to the turbulent flow in the so-called hydraulically transitional flow regime. The shear stress is estimated at onset of motion. Some illustrative results showing the strong impact of the angle of repose, and the exposure of the bead to shear flow are represented in both regimes.
Keywords: Granular Flow; Particle/Fluid Flow; Sediment Transport; Incipient Motion